2017
DOI: 10.1111/pde.13188
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis Suppurativa in Down Syndrome: A Case Series

Abstract: The presence of hidradenitis suppurativa in 38% of patients with Down syndrome is far higher than would be expected by chance alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…This finding is comparable with that of other authors [12] who detected a younger age in patients with HS and DS compared to those without DS (17.9 vs. 33.9 years; p < 0.001). In line with previous studies [10, 12], our 9 patients with HS and DS had a mild severity of the disease (Hurley stage I in 7 cases and Hurley stage II in 2 cases) and therefore they had been treated with topical corticosteroids and antibiotics, achieving a good control of the disease. No significant differences concerning sex, BMI, and comorbidities were found between patients with HS and DS compared to patients with HS only (Table 2).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This finding is comparable with that of other authors [12] who detected a younger age in patients with HS and DS compared to those without DS (17.9 vs. 33.9 years; p < 0.001). In line with previous studies [10, 12], our 9 patients with HS and DS had a mild severity of the disease (Hurley stage I in 7 cases and Hurley stage II in 2 cases) and therefore they had been treated with topical corticosteroids and antibiotics, achieving a good control of the disease. No significant differences concerning sex, BMI, and comorbidities were found between patients with HS and DS compared to patients with HS only (Table 2).…”
Section: Discussionsupporting
confidence: 60%
“…HS-related syndromes could be classified into three groups based on (1) the specific genetic background (presence of a pathognomonic test), (2) the presence of follicular plugging or structural disorders, and (3) a possible autoinflammatory pathogenesis. A syndromic condition including both HS and DS, and belonging to group 1, has been previously described, but only in a few studies [10-16]. In a retrospective study, Denny and Anadkat [12] found that 16 of 667 (2.4%) patients with HS were concomitantly affected by DS, showing that the prevalence of DS was about 29 times higher in HS patients compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidences are as follows: (i) family history is often negative; (ii) HS is more frequent in females; (iii) the age of HS onset is early; (iv) BMI values are often high; (v) the location of the lesions is more frequently below the diaphragm and (vi) the severity of HS is often mild . No conclusive data are available about the prevalence of HS in patients with DS; it ranged from 2.1% in a population‐based cross‐sectional analysis carried out in United States, to 3.5% in an Italian study, to 14.6% in a French cross‐sectional study and to 38% in a Saudi Arabian study . As regards the ethnicity, according to a study carried out in United States, HS was more frequent in non‐Caucasian DS subjects .…”
Section: Case Seriesmentioning
confidence: 99%
“…3,4,7 No conclusive data are available about the prevalence of HS in patients with DS; it ranged from 2.1% in a populationbased cross-sectional analysis carried out in United States, 6 to 3.5% in an Italian study, 7 to 14.6% in a French cross-sectional study 8 and to 38% in a Saudi Arabian study. 4 As regards the ethnicity, according to a study carried out in United States, HS was more frequent in non-Caucasian DS subjects. 3 However, in another American study, HS was more common in Caucasians with DS.…”
Section: Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation